Using the Parable of the Blind Men and the Elephant as a Pedagogical Tool for Teaching Religious Pluralism - Corpuz, Jeff Clyde (Teaching theology and religion, 2025)
This study explores the use of the parable of the blind men and the elephant as a pedagogical tool to foster interreligious understanding among college students. Drawing on this classic narrative—often used to illustrate the challenges of partial perspectives—the study examines how students engage with questions of faith and religious diversity in a classroom setting. Conducted at a Catholic university in a predominantly Christian country in Asia, the research employed a three-part method: presenting the parable, facilitating guided reflection questions, and using an online word cloud generator to synthesize collective insights. The goal of this strategy is to cultivate open-mindedness, mutual respect, and deeper appreciation for religious pluralism. Rather than claiming theological insights per se, the study investigates students' emerging attitudes and interpretations in dialogue with one another. The article reflects critically on the theological implications of the parable in light of critiques from theologians and argues for the value of narrative-based teaching in advancing interreligious literacy and constructive dialogue in higher education.